Examen especial a la cuenta de ingreso y gasto de la distribuidora ¨DELJAR¨ dedicada a la compra y venta de artículos de ferreteria, materiales y accesorios de construcción del canton Zamora, provincia de Zamora Chinchipe, en el periodo 2014 - Vicent Fernández, Germania Cleotilde (2016)
This research entitled "SPECIAL ACCOUNT OF INCOME AND SPENDING DEDICATED TO THE DISTRIBUTOR ¨DELJAR¨ buying and selling of hardware, BUILDING MATERIALS AND ACCESSORIES REVIEW OF CANTON ZAMORA, province of Zamora Chinchipe, IN THE PERIOD 2014." It was run to determine the accuracy and reasonableness of the accounts of income and expenses by applying a special test is important because it allowed us to know the movement of accounts analysis, profitability, liquidity and management. The work was based on the objective of analyzing the income and expenses of the company "DELJAR", in order to determine the legality and accuracy of accounting transactions, which was determined by reviewing the various documents livelihood of income and expenses. In a second objective the existing laws and regulations for the management of revenue and expenditure account, for it worked with the internal control regulations in force, as with internal regulations provisions was examined. The third objective of the final special examination report, which was made based on the findings in the accounts of revenue and expenditure of the company "DELJAR" socialized After completing the work it is concluded that the company DELJAR need to improve the control system of income and expenses due to deficiencies existing balances in the accounts with the revision made, so the owner is encouraged to note improve control Internal income and expenses.